National and International Systems of Broadcasting / Their History, Operation and Control - East Lansing; Emery Walter B (1969)
Acknowledgements, Foreword, Introduction, National Systems of Broadcasting, North and Central America, The United Kingdom and Ireland, The Benelux Countries, The Northern Countries, France and the Mediterranean Countries, The Middle European Countries, The Iberian Peninsula, The Soviet Union and Eastern Europe, The Middle East, Africa and Asia and Australia, International Broadcasting, Appendices, Bibliography, Index.